THE USE OF BLENDED LEARNING MODEL ON STUDENTS' LEARNING MOTIVATION AND CRITICAL THINKING ABILITIES - Ahmad Ahmad; A. Jauhar Fuad (International Conference on Humanity Education and Society (ICHES), 2025)
This article discusses the use of blended learning models on students' learning motivation and critical thinking skills. Blended learning, which combines face-toface learning with independent learning or class-based activities, has been proven to increase students' involvement and active participation in the learning process. This model provides opportunities for students to manage their own learning time while getting direct support from face-to-face teaching. In the context of learning motivation, blended learning provides variations in learning methods that can spur students' interest and enthusiasm for learning. In addition, this model also strengthens students' critical thinking skills through discussion, reflection, and collaborative problem solving. This article concludes that the application of the blended learning model can have a positive impact on developing students' learningmotivation and improving their critical thinking skills. With a more flexible and interactive approach, blended learning is an effective alternative in facing the challenges of learning in the modern era.